Rugged individualism and the misunderstanding of American inequality - Eppard, Lawrence M. (Lehigh University Press ; The Rowman & Littlefield Publishing Group, Inc., 2020)
"In Rugged Individualism and the Misunderstanding of American Inequality, the authors argue that a culture of individualism in the U.S. limits the pressure politicians face to develop robust social policies. This individualism combines with racism and features of the political system to help perpetuate high levels of poverty and inequality"--